Investigating the p--π± and p--p--π± dynamics with femtoscopy in pp collisions at s=13 TeV - Zurlo, N.; Zugravel, S.C.; Zhu, Y.; Zhu, S.; Zhu, J.; Zhou, Y.; Zhou, D.; Zhi, Y.; Zherebchevsky, V.; Zhao, M.; Zhang, Z.; Zhang, Y.; et al. (Springer, 2025)
Abstract The interaction between pions and nucleons plays a crucial role in hadron physics. It represents a fundamental building block of the low-energy QCD dynamics and is subject to several resonance excitations. This work studies the $$\text {p--}\uppi ^{\pm }$$ p-- π ± dynamics using femtoscopic correlations in high-multiplicity pp collisions at $$\sqrt{s} = 13$$ s = 13 TeV measured by ALICE at the LHC. As the final-state interaction between protons and pions is well constrained by scattering experiments and the study of pionic hydrogen, the results give access to information on the particle-emitting source in pp collisions using the femtoscopy methods. The scaling of the source size of primordial protons and pions against their pair transverse mass is extracted. The results are compared with the source sizes studied with p–p, $$\text {p--K}^+$$ p--K + , and $$\uppi ^\pm $$ π ± – $$\uppi ^\pm $$ π ± pairs by ALICE in the same collision system and are found to be in agreement for the different particle pairs. This reinforces recent findings by ALICE of a common emission source for all hadron-pairs in pp collisions at LHC energies. Furthermore, the $$\text {p--p--}\uppi ^{\pm }$$ p--p-- π ± systems are studied using three-particle femtoscopy in pp collisions at $$\sqrt{s} = 13$$ s = 13 TeV. The presence of three-body effects is analyzed utilizing the cumulant expansion method. In this formalism, the known two-body interactions are subtracted in order to isolate the three-body effects. For both, $$\text {p--p--}\uppi ^{+}$$ p--p-- π + and $$\text {p--p--}\uppi ^{-}$$ p--p-- π - , a non-zero cumulant is found, indicating effects beyond pairwise interactions. These results give information on the coupling of the pion to multiple nucleons.
Keywords: Physics; Particle physics; Dynamics (music); Nuclear physics; https://purl.org/pe-repo/ocde/ford#1.03.00